The Effect of Regional Trade Agreements on ASEAN Trade Flows - Yoshi Evelyn Nathania Dianzah (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2022)
The total number of Regional Trade Agreement (RTA) has increased rapidly over the past 30 years, from 22 in 1990 to 308 in 2020. The association of Southeast Asian Nations (ASEAN) aimed to increase regional integration among members through ASEAN Free Trade Area (AFTA) that came into force in 1993 and broadened its regional integration started in 2005 through trade agreements with China, Japan, Korea, Australia, New Zealand, and India. This paper study the impact of 5 ASEAN RTAs simultaneously to get comprehensive results. The Hausman-Taylor estimator was used to overcome endogeneity problems in the gravity equation without dropping the time-invariant variables which become the advantage of this method. The results show that AFTA increases trade flows between members and promotes imports and exports to the rest of the world. ASEAN regional integration outside the region with six trade partners show positive effect to members and has a minimal negative effect to non-members globally.